Intercultural politeness managing relations across cultures - Spencer-Oatey, Helen 1952-; Kádár, Dániel Z. 1979- (Cambridge University Press, 2021)
"It is increasingly important in our globalised world for people to successfully manage interpersonal relationships. This is the first book to tackle this vital topic, by taking an interdisciplinary approach to exploring the process of relating across cultures. Drawing together key concepts from politeness theory, intercultural communication, and crosscultural/ intercultural psychology, it provides a robust framework for analysing and understanding intercultural encounters. It explores the ways in which individuals make judgements about others, deal with offence and conflict, maintain smooth relations, and build new relationships. These processes are explained conceptually and illustrated extensively with authentic intercultural examples and empirical data. With accessible explanations and follow-up activities, it will appeal not only to academics working in the areas of intercultural communication, pragmatic theory, conflict research and other related academic disciplines, but also to students of these topics, as well as professionals such as intercultural trainers and those working in the third sector"--
Literaturverzeichnis Seite 350-376
Keywords: Interkulturelle Kompetenz; Kulturkontakt; Höflichkeit; Intercultural communication / Cross-cultural studies; Interpersonal relations / Cross-cultural studies; Courtesy